Biossorção e biodegradação do corante têxtil Guarany 16- azul marinho em meio aquoso por Saccharomyces cerevisiae - Toledo, Sabrina Monteiro (Universidade Federal de São Carlos, 2023)
Textile industries are responsible for excess amounts of dye waste discarded in water bodies, affecting the ecosystem. The chemical composition of these dyes makes them highly toxic compounds and harmful not only to the environment, but to public health, making bioremediation measures necessary. Biological treatment, when compared to others, demonstrates great potential due to savings, time, effectiveness and reduction of secondary waste. Among the techniques used for treatment, biosorption and biodegradation stand out. This work proposed using the yeast Saccharomyces cerevisiae as the main bioremediation agent for the dye Guarany 16- Marine Blue through adsorption and biodegradation processes. The adsorption process was evaluated by UV-VIS spectroscopy, based on triplicate tests at concentrations of 5, 10 and 15% of the dye, in solutions of pH 2.5 and 4.5 containing 100μl of live and dead yeast. The biodegradation tests occurred based on the evaluation of growth parameters in minimal YPD medium and dye in Petri dishes, in the dye solution with a concentration of 5%, determined according to the highest adsorption rate of the previous test, with a pH of 2.5. After reading by spectrophotometry, the values were analyzed and mean, median and standard deviation calculations were made in order to standardize the indices and obtain the constant of variation for developing the graphs. The results indicate that the best conditions for adsorption in solution were at pH 2.5, using live biomass, under agitation and at a temperature of 28ºC. The greatest removal efficiency was at a concentration of 5% dye. The maximum adsorption capacity in relation to the initial dye concentration was estimated at up to 70.20%. Furthermore, the yeast was able to biodegrade and grow in the medium during the period of exposure to the dye, demonstrating its bioremediation potential in the treatment of textile effluents.
Biosorption and biodegradation of the textile dye Guarany 16- navy blue in aqueous medium by Saccharomyces cerevisiae
Keywords: Efluente têxtil; Biorremediação; Espectrofotometria; Levedura; UV-VIS; Textile effluent; Bioremediation; Spectrophotometry; Yeast; CIENCIAS BIOLOGICAS::MICROBIOLOGIA